Breaking Gender Barriers : Vocational Training Vouchers and Kenyan Youth - Hicks, Joan Hamory; Kremer, Michael; Mbiti, Isaac; Miguel, Edward (World Bank, Washington, DC, 2016)
Youth account for approximately 60 percent of the unemployed population in Sub-Saharan Africa. Seventy two percent of adolescents in the region live below the $2/day poverty line. Vocational education has been identified as a promising avenue for young adults to acquire and develop marketable skills for employment. The Technical and Vocational Vouchers Program (TVVP) was launched in an attempt to fill key knowledge gaps in Kenya. The evidence suggests that: i) by nudging women to acquire training in lucrative male dominated trades; the information intervention may boost the earnings potential for women in vocational training. Additionally, ii) among those employed at the time of survey, students with vocational training were more generously compensated, with females enjoying the greatest financial returns amongst voucher recipients.